Teacher’s strategies in survival speaking learning during COVID-19 pandemic - Puspitasari, Dewi; Nofianto, Norma; Huda, Muhammad Ifanul (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This paper focuses on the teacher’s strategies during an online learning in Survival Speaking subject. Drawing on narrative inquiry, the paper describes and analyzes how a teacher deals with online learning from August to September 2020. The paper concludes that the teacher experienced challenges in teaching during the pandemic and he was stimulated to provide engaging learning by combining both synchronous and asynchronous mode of learning for his Survival Speaking students. The teaching practice was affected by his teaching philosophy and the implementation was in accordance to Vigotskian’ Zone of Proximal Development in conducting the learning during COVID-19 pandemic by providing help and support for the students before making sure the students would be ready in the real practice.